Determining of thermal time and base temperature during the reproductive phase of the Japanese plum in the tropical Andes (2024)
Climate factors affect the phenological behavior of Japanese plum (Prunus salicina Lindl.) cultivation in tropical elevation. Thermal time is more precise than chronological time for the cultivation labor program and for the estimation of crop phenological events. The objective of this study was to determine the base temperature (Tb) and thermal time for the development of the 'Horvin' plum fruit, estimating the Tb for the reproductive phenological phase of the plum. Twenty trees, consisting of ten trees per rowat two different elevations of 2,195 and 2,567 m a.s.l. (meters above sea level), in the municipality of Nuevo Colon (Colombia), were marked by locality. The appearance of each phenological stage was recorded from floral bud to harvest, estimating Tb with the minimum coefficient method of variation in function of growing degree day (GDD). The results show Tb for the phenological stages floral-anthesis with 2.84°C; anthesis-fruits set, 3.05 °C, and fruit set-harvest, 1.76°C. Therefore, this variety should be grown where there is a minimum temperature of 3.05°C during the reproductive phase. In addition, the results show that an average of 1,243.17 and 1,172.12 GDD is required to go from fruit set to fruit harvest at elevations 2,195 and 2,567 m a.s.l., respectively.